2019
DOI: 10.1002/clc.23188
|View full text |Cite
|
Sign up to set email alerts
|

Ankle‐brachial index, arterial stiffness, and biomarkers in the prediction of mortality and outcomes in patients with end‐stage kidney disease

Abstract: Background Although ankle‐brachial index (ABI) and brachial‐ankle pulse wave velocity (baPWV) are significant predictors of major adverse cardiovascular event (MACE), their prognostic value in association with biomarkers has not been fully evaluated in patients with end‐stage kidney disease (ESKD). Hypothesis We hypothesized that ABI/baPWV would provide better prognostic value independent of biomarkers in ESKD patients. Methods This study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…found that abnormal ABI (ABI < 0.9 or >1.4) was associated with major adverse cardiovascular events (all cause of death, acute coronary syndrome, and stroke). 24 In the present study, we found that decreased ABI level was significantly associated with IS and that those with abnormal ABI had a significantly higher risk of IS compared with those with normal ABI. The IMPACT-ABI study showed that the incidence of stroke was significantly higher in the low ABI (≤0.9) and borderline ABI (0.91–0.99) than those with normal ABI (1.00–1.40) in patients hospitalized for cardiovascular disease during a 4.8-year mean follow-up period.…”
Section: Discussionsupporting
confidence: 57%
“…found that abnormal ABI (ABI < 0.9 or >1.4) was associated with major adverse cardiovascular events (all cause of death, acute coronary syndrome, and stroke). 24 In the present study, we found that decreased ABI level was significantly associated with IS and that those with abnormal ABI had a significantly higher risk of IS compared with those with normal ABI. The IMPACT-ABI study showed that the incidence of stroke was significantly higher in the low ABI (≤0.9) and borderline ABI (0.91–0.99) than those with normal ABI (1.00–1.40) in patients hospitalized for cardiovascular disease during a 4.8-year mean follow-up period.…”
Section: Discussionsupporting
confidence: 57%
“…In Central Africa, HR estimates for low ABI (≤0.9) were 1.86 for mortality in a population aged ≥65 years, 10% of whom had diabetes and 7% whom had a history of myocardial infarction [32]. In Japan, HR estimates for abnormal ABI (<0.9 or >1.4) were 2.01 for major adverse cardiovascular events in a population with end-stage kidney disease, 38% of whom had diabetes and 28% whom had prior coronary revascularization [33]. In France, a HR for total mortality of 1.46 was reported in a population prior to coronary artery bypass grafting [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study population consisted of a primary prevention cohort, peripheral artery disease, which is a robust predictor of CVD outcomes ( 54 ), may influence the accurate measure of arterial stiffness. Otsuka et al ( 54 ) reported that the ankle-brachial index (ABI) indicates peripheral artery embolism, which might affect the measurement of arterial hardness and increase the risk of cardiovascular diseases. Also, a previous study showed that patients > 60 years with carotid plaques and low ABI (ABI 0.9) have a significantly increased risk of ischemic cardiovascular disease (HR = 7.16) ( 55 ).…”
Section: Discussionmentioning
confidence: 99%